INCREASING THE ACTIVENESS AND LEARNING OUTCOMES OF MATHEMATICS ON THE MATERIAL OF MATHEMATICAL SENTENCES AND CALCULATIONS THROUGH THE REALISTIC MATHEMATIC EDUCATION (RME) APPROACH FOR GRADE IV STUDENTS OF SDN 2 CEPEDAK - Yanti; Muflikhul Khaq; Rintis Rizkia Pangestika3 (Swakarya: Jurnal Penelitian Sosial dan Pengabdian Masyarakat, 2023)
Improving the Activeness and Learning Outcomes of Mathematics on Mathematical Sentences and Calculations Through the Realistic Mathematic Education (RME) Approach for Grade IV Students of SDN 2 Cepedak". Thesis. Elementary School Teacher Education. FKIP, University of Muhammadiyah Purworejo. 2023. This study aims to determine whether there is an effect of the realistic mathematics learning approach on the mathematics learning outcomes of fourth grade students of SDN 2 Cepedak, Bruno District, Purworejo Regency, Central Java. This type of research is Classroom Action Research. The research was conducted in the second semester of the 2022/2023 school year with the research subjects being fourth grade students of SDN 2 Cepedak with a total of 20 students. The data collection instruments used in this study consisted of interview sheets, observation sheets, and evaluation tests. The data collection techniques used were observation, tests, interviews, field notes, and documentation. The data obtained are student learning outcomes and observation of student activeness. This research uses qualitative data analysis and quantitative analysis. Based on the action research, it can be concluded that the RME learning approach can improve activeness and learning outcomes in the material of mathematical sentences and calculations in class IV SD.